Rancang Bangun Aplikasi Tryout Ujian Nasional Sekolah Menengah Pertama (SMP) Berbasis Android - Harmadya, Mentari; Made AryaSasmita, Gusti; Ayu Wirdiani, Ni Kadek (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi, 2015)
Evaluation of learning outcomes focus on the National Examination aims to assess the achievement of students of junior high school nationally in Indonesian Language, Mathematics, English and Science. Tryout activities held to train students in answering the questions of the National Exam. This study aims to create an application National Exam Tryout for Android. The development of t his application using hybrid application development with a website as a back-end system and an Android applications as a front-end system that works like a client-server process on a computer network. Tryout types that exist in this application adjusting to Tryout conventional with added features with more and varied question.Based on the results of application testing followed by 30 students of Junior High School, the results of the Tryout application for Android is appropriate and declared eligible with 93 % percentage to be used as tools to help students of Junior High School in preparation for the National Exam.
Keywords: Try out; Sekolah Menengah Pertama (SMP); Android; Hybrid App